Science and the garden : (John Wiley & Sons, Ltd, 2016)
This expanded and fully updated Third Edition of Science and the Garden includes two completely new chapters on important topics: Climate and Other Environmental Changes. Health, Wellbeing and Socio-cultural Benefits.